On Caputo-Hadamard Type Fractional Differential Equations with Nonlocal Discrete Boundary Conditions - Manigandan, Murugesan; Subramanian, Muthaiah; Duraisamy, Palanisamy; Gopal, Thangaraj Nandha (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper studies a new class of boundary value problems of Caputo-Hadamard fractional differential equations of order $ρ\in (2, 3]$ supplemented with nonlocal multi-point (discrete) boundary conditions. Existence and uniqueness results for the given problem have obtained by applying standard fixed-point theorems. Finally, two examples are given to illustrate the validity of our main results.